High-efficiency asymmetric transmission of linear polarized waves based on tri-layered metamaterial structure. Issue 12 (13th August 2021) - Long, Fei; Yu, Shixing; Kou, Na; Li, Xucheng; Ding, Zhao; Zhang, Zhengping
Abstract : In this work, a broadband polarization converter in transmission mode based on tri-layered metamaterial structure is proposed to realize asymmetric transmission and linear polarization conversion simultaneously. The proposed design model consists of a hexapolar split ring structure and two orthogonal sub-wavelength gratings embedded in two dielectric substrates. The appropriate parameters of the unit cell are optimized and selected. Sequentially, a prototype is fabricated and measured in order to confirm performance of the proposed design structure. The simulation and measurement results consistently demonstrate that the conversion polarization transmission coefficient is greater than 0.9 within the frequency region of 4.516.7 GHz, which is equivalent to 115% of the relative bandwidth. Based on the Fabry–Perot-like cavity theory, the working mechanisms of this structure have been discussed in detail. Thus, the proposed design structure is expected high potential applications in irreversible electromagnetic devices.